Manajemen Komunikasi Pendidikan pada Lembaga Pendidikan di Era Global - Sakirman Sakirman; Ruslan Ruslan; Sapril Sapril; Titiek Rohanah Hidayati; Erma Fatmawati (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Although educational communication management has become a strategic issue in facing globalization and digital transformation, previous studies have tended to discuss learning technology, organizational communication, or leadership separately, and therefore have not fully synthesized the interrelationships among communication management, digital literacy, leadership, organizational culture, and the quality of educational services. This study aims to analyze the contribution of educational communication management to improving the effectiveness of educational institutions, identify communication challenges in the global era, and formulate strategies for its development. This study used a qualitative approach with a conceptual literature study design. Data were obtained from 26 journal articles, 11 academic books, and 1 international institutional report relevant to educational communication, digital transformation, school leadership, digital literacy, and school-parent communication. Data were collected through documentation, analyzed using thematic content analysis, and validated through source triangulation. The results of the review show that well-planned communication management can strengthen coordination, transparency, stakeholder participation, decision-making, and organizational culture. The main challenges in its implementation include digital literacy gaps, information overload, hoaxes, data security, privacy, and the lack of integration among communication channels. The conclusion of this study affirms that educational communication management needs to be developed as a strategic system based on planning, digital technology, information ethics, communicative leadership, and continuous evaluation. These findings contribute to the development of educational management studies and have practical implications for educational institutions in formulating communication policies, strengthening digital competence, and building adaptive internal-external communication mechanisms.